Pengambilan Keputusan dalam Perspektif Islam - Moh. Syamsul Falah (Menara Tebuireng, 2017)
Decision making is the last stage in addressing an issue that will be dealt with by a leader. Therefore, the condition is as important in leadership, because any decision to be taken must contain a risk and how serious the risks contained on this consideration. At this stage also the difference between a person's character, he has the soul of leadership (pemimpin) or subordinate (bawahan). But it is also necessary to understand that decision-making is no stages or process, style and type of decision-making, and modalities to be followed so that the decision can be according to the wishes would be expected. Decision-making is also not only in the discussion of education management, but in Islam also discussed the importance of the discussion related to the decision-making